Analysis of Cadmium (Cd) Levels in Tilapia Fish (Oreochromis mossambicus) from Ponds in Palibelo - Nurwahdania, Nurwahdania; Khairuddin, Khairuddin; Yamin, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Fish are oceanic biota that are frequently utilized as signs of weighty metal contamination in waters. The purpose of this study was to determine the levels of cadmium (Cd) in tilapia from ponds in Palibelo and whether or not it is safe for consumption based on the Regulation of the Food and Drug Supervisory Agency (BPOM) No. 9 of 2022 concerning Requirements for Heavy Metal Contamination in Processed Food. Sampling was carried out by purposive sampling, at each station two fish samples were taken using floating nets. Samples were analyzed at the Health Laboratory, Testing and Calibration Center (BLKPK) of NTB Province. Data analysis was carried out by taking body parts, namely tilapia meat, then analyzing cadmium (Cd) levels using AAS. The results showed that cadmium levels in tilapia were still below the standard quality standards ranging from 0.0033-0.0057 mg/kg, with an average cadmium of 0.00465 mg/kg. Cadmium comes from household waste and modern waste carried by river currents. Environmental factors obtained temperature, pH, and salinity are in ideal conditions for the life of Tilapia fish. The conclusion is that Tilapia fish from fish farming in Palibelo is still suitable for consumption because it is still below the standard quality of 0.30 mg/kg.